Composite graphite material, preparation method thereof, pole piece, application and lithium ion battery
By forming a high-density composite cladding layer on the surface of graphite aggregate, the problem of degradation in the performance of graphite anode materials for lithium-ion batteries in fast charging and long circulation is solved, and high stability and excellent battery performance are achieved.
Patent Information
- Application Number
- CN202411982509.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The graphite anode materials of existing lithium-ion batteries have deteriorated performance during fast charging and long cycle use, especially the fragile solid electrolyte interface (SEI) film, resulting in capacity attenuation and shortened cycle life.
By using the preparation method of composite graphite materials, the high-density composite cladding layer is formed by mixing liquid asphalt and metal fluoride with graphite aggregate, and the stability and conductivity of the material are improved.
It realizes high stability, mechanical strength and electrical conductivity of composite graphite materials, reduces the impedance of lithium-ion batteries, and takes into account excellent first-time, capacity and fast charging performance.
Smart Images

Figure CN119725492A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite graphite material and a preparation method, a pole piece, an application and a lithium ion battery thereof. Background Art
[0002] With the rapid development of electric vehicles and energy storage, lithium-ion batteries have become a key technology to support green energy and sustainable transportation. Users have increasing demands for fast charging capabilities, long cycle life, and high energy density. However, the anode materials in existing lithium-ion battery technology, especially graphite anodes, face technical challenges of performance degradation under fast charging and long cycle conditions.
[0003] In the process of lithium ion insertion and deinsertion, the transport kinetics of lithium ions in traditional graphite negative electrode materials are relatively limited, resulting in insufficient lithium ion transport speed on the material surface under high-rate charge and discharge conditions, thus affecting the overall fast-charge performance of the battery. In addition, the solid electrolyte interface (SEI) film formed on the surface of the graphite negative electrode is relatively fragile during multiple charge and discharge cycles, and is easily damaged and decayed during long-term use, which leads to capacity decay and shortened cycle life. These problems have severely limited the widespread use of lithium-ion batteries in high-demand applications.
[0004] Existing technical methods for improving the performance of negative electrode materials for lithium-ion batteries are often limited to simple modification of the surface of graphite negative electrode materials. Although certain performance is improved in the short term, it cannot fundamentally solve the stability problems during long-term cycling and fast charging. For example, conventional SEI films are relatively fragile and easily affected by volume changes and chemical reactions during charge and discharge cycles, resulting in rapid degradation of battery performance. In addition, existing surface modification technologies sometimes reduce the conductivity of materials or the speed of lithium ion transmission, and cannot take into account the needs of improving first efficiency, reducing impedance and excellent capacity performance. Therefore, how to construct a stable SEI layer on the surface of graphite negative electrodes and improve lithium ion transmission kinetics in order to take into account improving first efficiency, reducing impedance and excellent capacity performance has become a core issue that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a composite graphite material and a preparation method thereof, a pole piece, an application and a lithium-ion battery. The composite graphite material has good stability, high mechanical strength and good conductivity, and the prepared lithium-ion battery has low impedance and can take into account excellent first efficiency, capacity performance and fast charging performance.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions.
[0007] The present invention provides a method for preparing a composite graphite material, which comprises the following steps:
[0008] S1. Mixing the composite coating agent and graphite aggregate uniformly to obtain a precursor; wherein the graphite aggregate comprises artificial graphite and / or natural graphite; the composite coating agent comprises liquid asphalt and metal fluoride; the mass ratio of the metal fluoride to the liquid asphalt is 1:(1-10); the mass ratio of the composite coating agent to the graphite aggregate is 1:(9-15);
[0009] S2. Carbonizing the precursor to obtain the composite graphite material.
[0010] In step S1, the liquid asphalt can be a liquid asphalt conventionally used in the art, preferably including one or more of modified asphalt, coal asphalt and solvent asphalt. Among them, solvent asphalt is a liquid asphalt material obtained by dissolving asphalt in an organic solvent. Modified asphalt is a liquid asphalt material obtained by adding fillers such as rubber, resin, and high molecular polymer to asphalt for modification.
[0011] In step S1, the metal fluoride preferably includes one or more of aluminum fluoride, iron fluoride, magnesium fluoride and calcium fluoride, for example, aluminum fluoride or iron fluoride.
[0012] In some embodiments, the metal fluoride is aluminum fluoride; wherein the aluminum fluoride is selected from one or both of the following conditions:
[0013] ① The aluminum fluoride contains crystal water, for example, aluminum fluoride trihydrate;
[0014] ② The aluminum fluoride is obtained by reacting an aluminum salt and an alkali metal fluoride or a quasi-alkali metal fluoride; wherein the aluminum salt preferably includes one or more of aluminum chloride, aluminum nitrate and aluminum acetate, such as aluminum nitrate; the alkali metal fluoride or a quasi-alkali metal fluoride preferably includes one or more of sodium fluoride, ammonium fluoride and potassium fluoride, such as ammonium fluoride.
[0015] In some specific embodiments, the metal fluoride is aluminum fluoride trihydrate.
[0016] In some specific embodiments, the metal fluoride is ferric fluoride.
[0017] In step S1, in the composite coating agent, the mass ratio of the metal fluoride to the liquid asphalt is preferably 1:(1.5-8), for example, 1:1.9, 1:3.8, 1:5.7 or 1:7.6.
[0018] In step S1, the mass ratio of the composite coating agent to the graphite aggregate is preferably 1:(9-14.5), for example, 1:9.1, 1:10.5, 1:12.7 or 1:14.1.
[0019] In step S1, the uniform mixing method may be a conventional uniform mixing method in the art, preferably a fusion process.
[0020] The fusion process is preferably carried out by a fusion machine, wherein the rotation speed of the fusion machine is 800-1100 r / min.
[0021] Wherein, the fusion treatment time is preferably 3-8 minutes.
[0022] In step S1, the method for preparing the composite coating agent may include the following steps: uniformly mixing the liquid phase asphalt and the metal fluoride to obtain.
[0023] In step S2, the temperature of the carbonization treatment may be 800-1200°C, preferably 900-1150°C, for example 1000°C or 1100°C.
[0024] In step S2, the heating rate to the temperature of the carbonization treatment may be 2-5°C / min, for example, 2.5°C / min.
[0025] In step S2, the carbonization treatment time may be 4-8 hours, for example, 6 hours.
[0026] In step S2, the carbonization treatment is preferably carried out by heating the temperature to 800-1200°C at a rate of 2-5°C / min and then maintaining the temperature for 4-8h.
[0027] In some specific embodiments, the carbonization treatment is carried out by heating the temperature to 1150° C. at a rate of 2.5° C. / min and then maintaining the temperature for 6 hours.
[0028] In some specific embodiments, the carbonization treatment is carried out by heating the temperature to 1000° C. at a rate of 2.5° C. / min and then maintaining the temperature for 6 hours.
[0029] In some specific embodiments, the carbonization treatment is carried out by heating the temperature to 900° C. at a rate of 2.5° C. / min and then maintaining the temperature for 6 hours.
[0030] In step S2, the carbonization treatment can be carried out in a carbonization treatment equipment conventionally used in the art, preferably in a track kiln.
[0031] In step S2, the carbonization treatment preferably further includes a screening treatment; preferably, the screening size of the screening treatment is 200-400 mesh.
[0032] The present invention provides a composite graphite material, which is prepared by the above-mentioned method for preparing the composite graphite material.
[0033] The present invention provides a composite graphite material, which comprises a core-shell structure, wherein the core-shell structure comprises an inner core and a composite coating layer coating the inner core; the inner core comprises artificial graphite and / or natural graphite; the composite coating layer comprises soft carbon, in which metal fluorides are distributed; wherein the mass ratio of the metal fluorides to the soft carbon is 1:(0.5-2); and the mass ratio of the composite coating layer to the inner core is (1.5-3):100.
[0034] In the present invention, the metal fluoride preferably includes one or more of aluminum fluoride, iron fluoride, magnesium fluoride and calcium fluoride, for example, aluminum fluoride or iron fluoride.
[0035] In the present invention, preferably, the soft carbon is obtained by carbonizing asphalt.
[0036] In the present invention, the mass ratio of the metal fluoride to the soft carbon is preferably 1:(0.5-1.5), for example, 1:1 or 1:1.2.
[0037] In the present invention, the mass ratio of the composite coating layer to the core is preferably (1.5-2.5):100, for example, 1.6:100, 1.8:100 or 2.2:100.
[0038] In the present invention, the mass ratio of the metal fluoride to the core may be (0.2-2.5):100, preferably (0.5-2):100, for example 1:100.
[0039] In the present invention, the mass ratio of the soft carbon to the inner core may be (0.1-3):100, preferably (0.5-2):100, for example 1:100.
[0040] In the present invention, the Dv10 particle size of the composite graphite material may be 9-10 μm, for example, 9.12 μm, 9.19 μm, 9.24 μm, 9.29 μm, 9.31 μm, 9.41 μm or 9.67 μm.
[0041] In the present invention, the Dv50 particle size of the composite graphite material may be 14-15 μm, for example, 14.08 μm, 14.27 μm, 14.36 μm, 14.45 μm, 14.48 μm, 14.54 μm, 14.57 μm, 14.56 μm or 14.82 μm.
[0042] In the present invention, the Dv90 particle size of the composite graphite material may be 22-24 μm, for example, 22.23 μm, 22.28 μm, 22.37 μm, 22.59 μm, 22.62 μm, 22.71 μm, 22.68 μm or 23.11 μm.
[0043] In the present invention, the specific surface area of the composite graphite material can be 1.1-1.4m 2 / g, preferably 1.1- <h2 style=";text-align:left;direction:ltr">1.3m<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> / g, For example, 1.16m 2 / g, 1.17m 2 / g, 1.18m 2 / g, 1.24m 2 / g, 1.25m 2 / g or 1.26m 2 / g.
[0044] In the present invention, the total pore volume of the composite graphite material can be 0.0045-0.0065 cm 3 / g, for example, 0.0047 cm 3 / g, 0.0050cm 3 / g, 0.0051cm 3 / g, 0.0052cm 3 / g, 0.0054cm 3 / g or 0.0055cm 3 / g.
[0045] In the present invention, the particle strength of the composite graphite material may be 0.91-0.93, for example, 0.915, 0.916, 0.917, 0.920, 0.921, 0.922 or 0.923.
[0046] In the present invention, the composite graphite material satisfying the above-mentioned structure, composition and performance parameters can be prepared by the aforementioned method for preparing the composite graphite material.
[0047] The present invention provides a pole piece, which comprises the composite graphite material as described above.
[0048] The present invention provides an application of the composite graphite material as described above as a negative electrode material in a lithium ion battery.
[0049] The present invention also provides a lithium ion battery, which comprises the composite graphite material as described above.
[0050] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0051] The reagents and raw materials used in the present invention are commercially available.
[0052] The positive and progressive effects of the present invention are:
[0053] In the present invention, metal fluoride and liquid phase asphalt are co-coated on the surface of graphite aggregate by a liquid phase coating process, and the obtained composite graphite material has a high-density composite coating layer; the composite graphite material has good stability, high mechanical strength and good conductivity. The lithium-ion battery obtained by using the composite graphite material as the negative electrode material has low impedance and can take into account excellent first efficiency, capacity performance and fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Schematic diagram of the structure of the composite graphite material obtained in Example 1 of the present invention.
[0055] Figure 2 This is a SEM picture of the composite graphite material obtained in Example 1 of the present invention.
[0056] Figure 3 This is a surface scanning image of the composite graphite material obtained in Example 1 of the present invention.
[0057] Figure 4 This is a C element distribution diagram of the composite graphite material obtained in Example 1 of the present invention.
[0058] Figure 5 This is the Al element distribution diagram of the composite graphite material obtained in Example 1 of the present invention.
[0059] Figure 6 This is the F element distribution diagram of the composite graphite material obtained in Example 1 of the present invention.
[0060] Reference numerals:
[0061] Soft Carbon 1
[0062] Aluminum fluoride 2
[0063] Artificial graphite 3 DETAILED DESCRIPTION
[0064] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0065] In the following examples and comparative examples, the liquid phase asphalt is solvent asphalt purchased from Liaoning Xinde New Materials Technology Co., Ltd., with a coking value of 0.16 and a density of 1.0±0.5 g / cm 2 , sulfur content is less than or equal to 0.15%, and ash content is less than 0.03%.
[0066] Example 1
[0067] The method for preparing the composite graphite material in this embodiment comprises the following steps:
[0068] S1-1, mixing aluminum fluoride trihydrate and liquid asphalt in a mass ratio of 1:7.6, and stirring evenly to obtain a composite coating agent;
[0069] S1-2, mixing the composite coating agent and artificial graphite in a mass ratio of 1:14.1 to obtain a mixed material, wherein the Dv50 particle size of the artificial graphite is 13.24 μm;
[0070] S1-3, putting the above mixed material into a fusion machine, setting the process parameters to a speed of 900r / min, a processing time of 8min, and discharging the material to obtain a precursor;
[0071] S2. The precursor is put into a track kiln, and the temperature is increased to 1150°C at a rate of 2.5°C / min, and the temperature is kept constant for 6 hours for carbonization. The material is cooled and discharged. After mixing and 300 mesh screening, a composite graphite material is obtained.
[0072] The structural schematic diagram of the obtained composite graphite material is shown in Figure 1 As shown, it includes an inner core and a composite coating layer covering the inner core, the inner core includes artificial graphite 3, the composite coating layer includes soft carbon 1, and aluminum fluoride 2 is distributed in the soft carbon 1.
[0073] Example 2
[0074] The difference between this embodiment and embodiment 1 is that in step S1-1, the mass ratio of aluminum fluoride trihydrate to liquid asphalt is 1:3.8, and the other conditions are consistent with those in embodiment 1.
[0075] Example 3
[0076] The difference between this embodiment and embodiment 1 is that in step S1-1, the mass ratio of aluminum fluoride trihydrate to liquid asphalt is 1:1.9, and the other conditions are consistent with those in embodiment 1.
[0077] Example 4
[0078] The only difference between this embodiment and embodiment 1 is that in step S1-1, the mass ratio of aluminum fluoride trihydrate to liquid asphalt is 1:5.7, and the other conditions remain the same as those in embodiment 1.
[0079] Example 5
[0080] The difference between this embodiment and embodiment 1 is that in step S1-1, ferric fluoride is used to replace aluminum fluoride trihydrate, and the other conditions are consistent with those in embodiment 1.
[0081] Example 6
[0082] The difference between this embodiment and embodiment 1 is that in step S2, only the carbonization temperature is changed to 900°C, and the other conditions remain the same as those in embodiment 1.
[0083] Example 7
[0084] The difference between this embodiment and embodiment 1 is that in step S2, only the carbonization temperature is changed to 1000°C, and the other conditions remain the same as those in embodiment 1.
[0085] Example 8
[0086] The difference between this embodiment and embodiment 1 is that in step S1-2, only the mass ratio of the composite coating agent to the graphite aggregate is changed to 1:10.5, and the other conditions remain the same as those in embodiment 1.
[0087] Example 9
[0088] The difference between this embodiment and embodiment 1 is that in step S1-2, only the mass ratio of the composite coating agent to the graphite aggregate is changed to 1:12.7, and the other conditions remain the same as those in embodiment 1.
[0089] Comparative Example 1
[0090] The preparation method of the composite graphite material in this comparative example comprises the following steps:
[0091] (1) mixing liquid asphalt and artificial graphite in a mass ratio of 1:16 to obtain a mixed material, wherein the Dv50 particle size of the artificial graphite is 13.24 μm;
[0092] (2) putting the above mixed material into a fusion machine, setting the process parameters to a speed of 900 r / min and a processing time of 8 min, and discharging the material to obtain a precursor;
[0093] (3) The precursor is placed in a track kiln, heated to 1150°C at a rate of 2.5°C / min, kept at a constant temperature for 6 hours, carbonized, cooled and discharged, mixed, and sieved with 300 mesh to obtain a composite graphite material.
[0094] Comparative Example 2
[0095] The preparation method of the composite graphite material in this comparative example comprises the following steps:
[0096] (1) dissolving 536 g of aluminum nitrate nonahydrate in 500 ml of deionized water to obtain an aluminum nitrate solution; dissolving 159 g of ammonium fluoride in 1000 ml of deionized water to obtain an ammonium fluoride solution;
[0097] (2) Slowly pour the ammonium fluoride solution in step (1) into the aluminum nitrate solution in step (1), and stir continuously for 20 minutes or more to obtain an aluminum fluoride precursor solution.
[0098] (3) mixing the aluminum fluoride precursor liquid obtained in step (2) and artificial graphite in a mass ratio of 1:5.5 to obtain a mixed material, wherein the Dv50 particle size of the artificial graphite is 13.24 μm;
[0099] (4) putting the above mixed material into a fusion machine, setting the process parameters to a speed of 900 r / min and a processing time of 8 min, and discharging the material to obtain a precursor;
[0100] (5) The precursor is placed in a track kiln, heated to 1150°C at a rate of 2.5°C / min, kept at a constant temperature for 6 hours, carbonized, cooled and discharged, mixed, and sieved with 300 mesh to obtain a composite graphite material.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 1 is that aluminum fluoride trihydrate is not used, and in step S1-2, liquid asphalt and graphite aggregate are directly mixed in a mass ratio of 1:14.1, and the other conditions are consistent with Example 1.
[0103] Effect Example 1
[0104] The composite graphite materials of Examples 1-9 and Comparative Examples 1-3 were tested using the following method:
[0105] (1) Dv10, Dv50 and Dv90 particle sizes
[0106] Malvern laser particle size tester MS3000 was used to test the Dv10 particle size, Dv50 particle size and Dv90 particle size of the composite graphite material. The test results are shown in Table 1.
[0107] (2) Specific surface area and total pore volume
[0108] The specific surface area and total pore volume of the material were tested using the fully automatic specific surface area and pore size analyzer NOVAtouchTM produced by Quantachrome Instruments, Inc. The test results are shown in Table 1.
[0109] (3) Particle strength: ratio of the Dv50 particle size of the sample under 2T powder compression to the Dv50 particle size before powder compression.
[0110] (4) Morphology
[0111] Thermo Fisher Scientific's scanning electron microscope Prisma was used to observe the sample morphology, particle size, etc. The obtained SEM images are shown in Figure 2 The EDS test results of the composite graphite material obtained in Example 1 are as follows: Figure 3-6 As shown, it can be seen that C, Al, and F elements are evenly distributed on the graphite surface.
[0112] (5) Calculation method of the mass of metal fluoride and soft carbon in composite graphite materials
[0113] The coking value of liquid phase asphalt is 0.16. After carbonization, the mass of soft carbon in the composite graphite material = the amount of liquid phase asphalt added × the coking value of liquid phase asphalt;
[0114] The mass of metal fluoride, taking aluminum fluoride as an example: after carbonization, the crystal water in aluminum fluoride trihydrate will volatilize. In the composite graphite material, the mass of aluminum fluoride = the mass of aluminum fluoride trihydrate × 61.3%.
[0115] The aluminum fluoride in Comparative Example 2 is prepared by using 2.86 mol / L aluminum nitrate nonahydrate solution and 2.79 mol / L ammonium fluoride solution to obtain a 0.93 mol / L aluminum fluoride solution. The mass of aluminum fluoride = the volume of the 0.93 mol / L aluminum fluoride solution × 83.974 g / mol.
[0116] Effect Example 2
[0117] Preparation of negative electrode sheet and lithium-ion battery
[0118] The composite graphite materials prepared in Examples 1-9 and Comparative Examples 1-3 were used as negative electrode materials, the composite graphite material, a binder (CMC and SBR, mass ratio of 1.5:1.5) and a conductive agent SP were mixed in a mass ratio of 95.5:3:1.5 (a total of 100 g), and 130 g of deionized water was added to mix to obtain a negative electrode slurry, and the negative electrode slurry was coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet;
[0119] Electrolyte formula: mixed solvent volume ratio of ethyl carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1, LiPF6 concentration is 1 mol / L;
[0120] A polypropylene microporous membrane was used as the separator and a metal lithium sheet was used as the positive electrode, and button cells were assembled in an inert gas glove box system filled with argon.
[0121] The charge and discharge test of button batteries was carried out on the LAND battery test system of Wuhan Landian Electronics Co., Ltd. The charge and discharge test of button batteries was carried out on the battery test system at room temperature, with a constant current of 0.1C and a charge and discharge voltage limit of 0.005 to 2V. The electrical performance data is shown in Table 2.
[0122] The specific test method is as follows:
[0123] (1) EIS test:
[0124] The prepared battery was first discharged at a rate of 0.2C to 0.005V, then discharged at a constant voltage of 0.005V to a current ≥ 0.05mA, and then charged at a rate of 2C for 15min. After activation, EIS test was performed on an electrochemical workstation (EC-lab).
[0125] (2) Charging capacity:
[0126] The prepared battery was first discharged at a rate of 0.2C to 0.005V, and then charged at a rate of 0.1C to 2V to obtain the charge specific capacity.
[0127] (3) First coulombic efficiency (%): first cycle discharge capacity / charge specific capacity × 100.
[0128] (4) Rate performance:
[0129] The prepared battery was first discharged at a rate of 0.2C to 0.005V, then charged at a rate of 0.2C to 2V, then discharged at 0.5C, charged at 0.2C, discharged at 1C, charged at 0.2C, discharged at 2C, charged at 0.2C, discharged at 3C, charged at 0.2C, the discharge capacity was tested, and the capacity retention rate at 3C was calculated. Wherein, the capacity retention rate at 3C (%) = 3C discharge capacity / 0.2C discharge capacity × 100.
[0130] Table 1 Related parameters of composite graphite materials
[0131]
[0132] Table 2 Electrochemical properties of lithium-ion batteries
[0133]
[0134]
[0135] As shown in Table 1, the Dv50 particle size of the composite graphite material obtained in Examples 1-9 of the present invention is between 14.08-14.82 μm, which is significantly larger than the Dv50 particle size of 13.24 μm of the artificial graphite used as graphite aggregate, indicating that the thickness of the composite coating layer is approximately between 1-2 μm. The Dv10 particle size of the composite graphite material obtained is between 9.12-9.67 μm, the Dv90 particle size is between 22.23-23.11 μm, and the specific surface area is between 1.10-1.26 m 2 / g, and the total pore volume is between 0.0045-0.0055cm 3 / g, the particle strength is between 0.910-0.923, and the particle strength and total pore volume of the obtained composite graphite material are small, which may be because the composite coating layer of the composite graphite material is relatively dense.
[0136] As shown in Table 2, the lithium-ion battery obtained by using the composite graphite material obtained in Examples 1-9 of the present invention as the negative electrode material has a low impedance and can take into account excellent capacity performance, first coulomb efficiency and fast charging performance. Specifically, the EIS of the lithium-ion battery can reach below 5.7Ω, or even below 5Ω; the charge specific capacity can reach above 349mAh / g; the first coulomb efficiency can reach above 90.8%; and the capacity retention rate at 3C can reach above 5.4%.
[0137] Compared with Example 1, in Comparative Examples 1 and 3, only liquid asphalt is used as a coating agent alone, and the EIS of the lithium ion battery obtained by using the obtained composite graphite material as the negative electrode material is significantly improved, and the charging specific capacity, the first coulomb efficiency and the capacity retention rate at 3C are all poor. Even if the same amount of coating agent relative to the graphite aggregate as in Example 1 is used in Comparative Example 3, the above effect is significantly poor. This may be because the composite coating layer of the composite graphite material obtained in Example 1 can regulate the SEI layer, thereby improving the first coulomb efficiency, and can effectively reduce the interface transfer impedance, promote the rapid diffusion of lithium ions, and the fast charging capability is also excellent.
[0138] Compared with Example 1, in Comparative Example 2, only aluminum fluoride is used as a coating agent, the particle strength of the obtained composite graphite material is significantly improved, the stability is poor, the EIS of the prepared lithium ion battery is high, and the charging specific capacity, the first coulombic efficiency and the capacity retention rate at 3C are poor.
[0139] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite graphite material, characterized in that: It includes the following steps: S1. Mixing the composite coating agent and graphite aggregate uniformly to obtain a precursor; wherein the graphite aggregate comprises artificial graphite and / or natural graphite; the composite coating agent comprises liquid asphalt and metal fluoride; the mass ratio of the metal fluoride to the liquid asphalt is 1:(1-10); the mass ratio of the composite coating agent to the graphite aggregate is 1:(9-15); S2. Carbonizing the precursor to obtain the composite graphite material.
2. The method for preparing a composite graphite material according to claim 1, characterized in that: In step S1, the liquid phase asphalt includes one or more of modified asphalt, coal asphalt and solvent asphalt; And / or, in step S1, the coking value of the liquid phase asphalt is 0.1-0.3, for example, 0.16; And / or, in step S1, the density of the liquid phase asphalt is 0.5-1.5 g / cm 2 ; And / or, in step S1, the sulfur content of the liquid phase asphalt is less than or equal to 0.15%, where the percentage is the mass percentage of the liquid phase asphalt; And / or, in step S1, the ash content of the liquid phase asphalt is less than 0.03%, where the percentage is the mass percentage of the liquid phase asphalt; And / or, in step S1, the metal fluoride includes one or more of aluminum fluoride trihydrate, iron fluoride, magnesium fluoride and calcium fluoride, for example, aluminum fluoride trihydrate or iron fluoride; And / or, in step S1, in the composite coating agent, the mass ratio of the metal fluoride to the liquid asphalt is 1:(1.5-8), for example, 1:1.9, 1:3.8, 1:5.7 or 1:7.6; And / or, in step S1, the mass ratio of the composite coating agent to the graphite aggregate is 1:(9-14.5), for example, 1: 9.1, 1:10.5, 1:12.7 or 1:14.1; And / or, in step S1, the uniform mixing method is fusion treatment; the fusion treatment is preferably performed by a fusion machine; the fusion treatment time is preferably 3-8 minutes; Wherein, the rotation speed of the fusion machine is preferably 800-1100r / min; And / or, in step S1, the preparation method of the composite coating agent comprises the following steps: uniformly mixing the liquid asphalt and the metal fluoride to obtain.
3. The method for preparing the composite graphite material according to claim 1, characterized in that: In step S2, the temperature of the carbonization treatment is 800-1200°C, preferably 900-1150°C, for example 1000°C or 1100°C; and / or, the heating rate to the temperature of the carbonization treatment is 2-5°C / min, for example, 2.5°C / min or 2.7°C / min; And / or, in step S2, the carbonization treatment time is 4-8 hours, for example, 6 hours or 7 hours; And / or, in step S2, the carbonization treatment is carried out by heating at 2-5°C / min to 800-1200°C and maintaining the temperature for 4-8h; Preferably, the carbonization treatment is carried out by heating the temperature at a rate of 2.5°C / min to 1150°C for 6 hours; Preferably, the carbonization treatment is carried out by heating the temperature to 900°C at a rate of 2.5°C / min and maintaining the temperature for 6 hours; Preferably, the carbonization treatment is carried out by heating the temperature to 1000°C at a rate of 2.5°C / min and maintaining the temperature for 6 hours; and / or, in step S2, the carbonization treatment is carried out in a track kiln; And / or, in step S2, the carbonization treatment further includes a screening treatment; preferably, the screening size of the screening treatment is 200-400 mesh.
4. A composite graphite material, characterized in that: The composite graphite material is prepared by the method for preparing the composite graphite material according to any one of claims 1 to 3.
5. A composite graphite material, characterized in that: It includes a core-shell structure, which includes an inner core and a composite coating layer coating the inner core; the inner core includes graphite aggregate; the graphite aggregate includes artificial graphite and / or natural graphite; the composite coating layer includes soft carbon, in which metal fluorides are distributed; wherein the mass ratio of the metal fluoride to the soft carbon is 1:(0.5-2); the mass ratio of the composite coating layer to the inner core is (1.5-3):
100.
6. The composite graphite material according to claim 5, characterized in that The metal fluoride includes one or more of aluminum fluoride, iron fluoride, magnesium fluoride and calcium fluoride, for example, aluminum fluoride or iron fluoride; And / or, the soft carbon is obtained by carbonizing liquid phase asphalt; And / or, the mass ratio of the metal fluoride to the soft carbon is 1:(0.5-1.5), for example, 1:1 or 1:1.2; And / or, the mass ratio of the composite coating layer to the core is (1.5-2.5):100, for example, 1.6:100, 1.8:100 or 2.2:100; And / or, the mass ratio of the metal fluoride to the core is (0.2-2.5):100, preferably (0.5-2):100, for example 1:100; And / or, the mass ratio of the soft carbon to the inner core is (0.1-3):100, preferably (0.5-2):100, for example 1:
100.
7. The composite graphite material according to claim 5, characterized in that The Dv10 particle size of the composite graphite material is 9-10 μm, for example, 9.12 μm, 9.19 μm, 9.24 μm, 9.29 μm, 9.31 μm, 9.41 μm or 9.67 μm; And / or, the Dv50 particle size of the composite graphite material is 14-15 μm, for example, 14.08 μm, 14.27 μm, 14.36 μm, 14.45 μm, 14.48 μm, 14.54 μm, 14.57 μm, 14.68 μm or 14.82 μm; And / or, the Dv90 particle size of the composite graphite material is 22-24 μm, for example, 22.23 μm, 22.28 μm, 22.37 μm, 22.59 μm, 22.62 μm, 22.71 μm, 22.68 μm or 23.11 μm; And / or, the specific surface area of the composite graphite material is 1.1-1.4m 2 / g, preferably 1.1-1.3m 2 / g, for example, 1.16m 2 / g, 1.17m 2 / g, 1.18m 2 / g, 1.24m 2 / g, 1.25m 2 / g or 1.26m 2 / g; And / or, the total pore volume of the composite graphite material is 0.0045-0.0065cm 3 / g, for example, 0.0047 cm 3 / g, 0.0050cm 3 / g, 0.0051cm 3 / g, 0.0052cm 3 / g, 0.0054cm 3 / g or 0.0055cm 3 / g; And / or, the particle strength of the composite graphite material is 0.91-0.93, for example, 0.915, 0.916, 0.917, 0.920, 0.921, 0.922 or 0.
923.
8. A pole piece, characterized in that: It comprises the composite graphite material according to any one of claims 4 to 7.
9. Use of the composite graphite material according to any one of claims 4 to 7 as a negative electrode material in a lithium ion battery.
10. A lithium ion battery, characterized in that: It comprises the composite graphite material according to any one of claims 4 to 7.